Elizabethan diplomacy and epistolary culture - Williamson, Elizabeth R. (Routledge, 2021)
"A new account of Elizabethan diplomacy with an original archival foundation, this book examines the world of letters underlying diplomacy and political administration by exploring a new material text never before studied in its own right: the diplomatic letter-book"--
Keywords: Geschichte 1558-1603; Auslandsbeziehungen; Diplomatische Beziehungen; Brief; Großbritannien; Great Britain / Foreign relations / 1558-1603; Diplomatic and consular service, British / History / 16th century; Diplomats / Great Britain / Correspondence / History / 16th century; Ambassadors / Great Britain / Correspondence / History / 16th century; Diplomatic and consular service, British; Diplomacy; Diplomatic documents; Diplomatic relations; Great Britain; 1500-1603; History; Sources